Análise dos registros de curativos em prontuários de um hospital de ensino do Estado de Goiás - Lemos, Lucimeire Fermino (2016)
Health records are important for keeping effective communication among all professionals involved in the process of taking care as well as for legitimating the team actions in the face of patients and families. The records must be clear and objective because they are sources of information for judicial, research, teaching, billing and auditing issues. This study has an objective to analyze the records of procedures of Level II Curative in medical records of hospitalized patients, from the nurses’ perspective, before and after the pedagogical intervention, in a Brazilian teaching hospital in the Midwest region. It was a descriptive study with both qualitative and quantitative research and was developed in many stages. The first stage included the nurses’ profiles and the identification of the main reasons why the nursing actions were not recorded. The second stage was the analysis of the records before and after the pedagogical action, which was the third stage. At last, the nurses were interviewed about their perception of the importance of the records for billing. It was observed among the sample of nurses the predominance of women (87,2%), post-graduated (82,1%) and statuary civil servants (80,4%). Even though 53,6% of the nurses said that they do not have double employment relationships, 46,4% said they do. The nurses said that it was not possible to record the procedures due to lack of time (50%), work overload (20%), lack of human resources and access to the records (12,5%), interruptions and lack of guidance (2,5%). The objective of the intervention was to discuss the importance of health records, and specially, in relation to the level II curative. 45,2% of the nurses of this institution took part in this event. In the analysis of the records, before and after the intervention, it was possible to observe the increase of the records of the curatives (82,3%), the detailing of the quantity of curatives per patient (69,9%), the classification of the wounds (63,5%), the description of the materials used in the procedures (67,3%), and also the scheduling (74%) and the checking (71,4%). The data shows that the quantity of material used maintained still. However, there was a rise of curative prescription by the nurses (79,4%) and a fall of curative prescription by the doctors (18,3%). It was also possible to observe that the performed and not prescribed procedures or prescribed and not verified procedures, in both cases, were not billed. Nevertheless, the hospital overturn related to this procedure has an increase, from July 2015. The interviews with the nurses showed that they take the responsibility in the treatment of wounds for themselves. However, it is necessary to standardize the prescriptions and the evolutions of the procedure. The complete record of this intervention is important to safeguard the institution in case of auditing. In conclusion, nurses have an important role in recording the wound treatment. The obligation of recording should be reinforced due to the quality of the service and the profession´s visibility as well as for a better material and input control and billing.